Selecting Potential Water Harvest Sites Using GIS and Remote Sensing In Al-Tharthar Valley, West Nineveh, Iraq. - Mahmood A. H. Al-Ardeeni (Tikrit Journal of Pure Science, 2023)
The main justification of this research is that integrate of GIS technique and RS data to generate maps for selecting the most potential sites of water harvesting in study area. This method helps to detect water harvesting sites in suitable places and improve the water resource management in the study area. The methodology was adopted in this study is using Fuzzy logic Modelling to standardise the layers and Fuzzy overlay method to combine and process these layers together. Specific criteria were used to standardise all these layers. Seven different criteria were used in this research to select the water harvesting sites such as slope (%), stream network (order), rainfall (mm), soil (type), distance to roads and urban centre and Normalised Difference Vegetation Index (NDVI). This research is significant because it is associated with several fields such as agriculture productivity, livestock husbandry, sustainable environment, soil fertility, water management, human livelihood and the agriculture industry. The outcomes of this research are to produce map of potential water harvesting sites in Al-Therthar valley, West Nineveh. This will give opportunity to build dams to store the water in particular in drought-stricken areas. This study found that there are 16 sites within the study area that represent the best potential water-harvesting sites. These sites were chosen according to the specific criteria that were used for this purpose and had a high potential in terms of their suitability for water harvesting.